The Use of Dysphemism in the Comments Column on the Instagram Account @stateofisrael - Fasa, Faradila Awalia; I Dewa Putu Wijana (International Journal of English Linguistics, Literature, and Education (IJELLE), 2024)
The use of dysphemism expressions is generally used with the aim of being able to express someone's thoughts using words or phrases that have negative connotations and sound impolite or rude, so the use of dysphemism expressions is intended as a form of expressing anger, annoyance, disappointment or hatred towards someone. This study uses qualitative methods. The data source in this study is comments in the comments’ column on the Instagram account @stateofisrael. The result was the linguistic form; three lingual forms were found: primary word, phrase, and clause. Then, this study also found that there are nine functions of using dysphemism expressions, including 1) expressing anger or irritation, 2) criticizing, 3) insinuating, 4) insulting, mocking, or sharpening insults, 5) accusing or blaming, 6) complaining, 7) conveying information, 8) showing disagreement, and 9) showing dislike. Thus, dysphemism expressions express thoughts and emotions towards someone or something by choosing words or terms that can hurt the interlocutor's feelings.